PENGARUH MEKANISME TATA KELOLA PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP STRUKTUR MODAL (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2013) - Reminov, Melvin Mikha; Hadiprajitno, Paulus Basuki (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of corporate governance mechanisms and ownership structure to capital structure. The dependent variable is capital structure which is proxied as debt ratio (DR). Independent variable are corporate governance mechanism which is proxied by size of the board of commissioners, size of the board of independent commissioners, size of the board of directors, size of the audit committee. Ownership structure which is proxied by managerial ownership and institutional ownership. This study was used secondary data from annual reports of manufacturing companies which were listed on Indonesia Stock Exchange in 2011-2013. Samples were 40 manufacturing companies. This study used purposive sampling method and multiple linear regression as the analysis method. Before being conducted by regression test, it was examined by using the classical assumption tests. The results of this study indicate that the size of the board of commisioners, size of the board of independent commisioners, size of board committee, and institusional ownership did not have significant influence to the agency cost. The size of the board of directors and managerial ownership have significant influence to capital structure.